Post-ST-Segment Elevation Myocardial Infarction Follow-Up Care During the COVID-19 Pandemic and the Possible Benefit of Telemedicine: An Observational Study - Zhang, Audrey A. Y.; Chew, Nicholas W. S.; Ng, Cheng Han; Phua, Kailun; Aye, Yin Nwe; Mai, Aaron; Kong, Gwyneth; Saw, Kalyar; Wong, Raymond C. C.; Kong, William K. F.; Poh, Kian-Keong; Chan, Koo-Hui; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Infectious control measures during the COVID-19 pandemic have led to the propensity towards telemedicine. This study examined the impact of telemedicine during the pandemic on the long-term outcomes of ST-segment elevation myocardial infarction (STEMI) patients. Methods This study included 288 patients admitted in the one year before the pandemic (October 2018–December 2018) and during the pandemic (January 2020–March 2020) eras, and survived their index STEMI admission. The follow-up period was 1 year. One-year primary safety endpoint was all-cause mortality. Secondary safety endpoints were cardiac readmissions for unplanned revascularisation, nonfatal myocardial infarction, heart failure, arrhythmia, unstable angina. Major adverse cardiovascular events (MACE) was defined as the composite outcome of each individual safety endpoint. Results Despite unfavourable in-hospital outcomes among patients admitted during the pandemic compared to pre-pandemic era, both groups had similar 1-year all-cause mortality (11.2% vs 8.5% respectively, p=0.454) but higher cardiac-related (14.1% vs 5.1%, p<0.001) and heart failure readmissions in the pandemic versus pre-pandemic groups (7.1% vs 1.7%, p=0.037). Follow-up was more frequently conducted via teleconsultations (1.2 vs. 0.2 per patient/year, p=0.001), with reduction in physical consultations (2.1 vs. 2.6 per patient/year, p=0.043), during the pandemic versus pre-pandemic era. Majority achieved guideline-directed medical therapy (GDMT) during pandemic versus pre-pandemic era (75.9% vs 61.6%, p=0.010). Multivariable Cox regression demonstrated achieving medication target doses (HR 0.387, 95% CI 0.164-0.915, p=0.031) and GDMT (HR 0.271, 95% CI 0.134-0.548, p<0.001) were independent predictors of lower 1-year MACE after adjustment. Conclusion The pandemic has led to the wider application of teleconsultation, with increased adherence to GDMT, enhanced medication target dosing. Achieving GDMT was associated with favourable long-term prognosis.